Web-Based Bag And Luggage Sales Information System At CV. Purnama - Farid Musyafa’; Sumarno (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to design and create a web-based information system that functions to help manage the sales process at CV. Purnama. This research was conducted in March 2020 at the Informatics Laboratory, University of Muhammadiyah Sidoarjo and CV. Purnama. This research was conducted using the waterfall method, data were collected through interviews, literature study, and problem analysis. The results of this study are the design and manufacture of Web-Based Bag and Suitcase Sales Information Systems at CV. Purnama which aims to increase promotion and facilitate the operational management in CV. Purnama. This information system has two actors, namely admin as manager of information systems and customers as consumers. Based on this research, the conclusion is that with the sales system (e-commerce), CV. Purnama can facilitate the conventional transaction process to become more modern with the availability of online transactions.